Corporate Social Responsibility Berdasarkan Pendekatan Economic Analysis Of Law - Melandito Marakey; Rr. Ani Wijayati; Johnson SMT Pangaribuan (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Corporate Social Responsibility (CSR) or in Article 1 number 3 of the Company Law is referred to as Social and Environmental Responsibility, which aims to develop the local community or society in general. Furthermore, the regulation regarding CSR is regulated again in Article 74 paragraph (1), which stipulates that only PTs engaged in or related to natural resources are required to carry out CSR. This raises a consequence, that PTs that are not active or related to natural resources are not required to carry out CSR. The CSR arrangements in Article 74 paragraph (1) then become inconsistent with the 3rd paragraph of the Preamble to the 1945 Constitution of the Republic of Indonesia which talks about welfare and prosperity and is also inconsistent with the 5th precept of Pancasila which talks about social justice for all. people of Indonesia. The formulation of the problem in this thesis is why there are differences in CSR obligations for companies engaged in or related to natural resources and companies that are not engaged in or related to natural resources, and How is the application of EAL to CSR arrangements is in the Company Law. This research is normative legal research with a conceptual approach and a statutory approach. The data used is secondary data in the form of primary legal materials: the 1945 Constitution of the Republic of Indonesia, Law Number 40 of 2007 concerning Limited Liability Companies, Law Number 32 of 2009 concerning Environmental Protection and Management, Law Number 12 of 2011 concerning the Formation of Legislation, while secondary legal materials are obtained from books, journals, theses, and other literature. From the results of the study, it was concluded that the provisions referred to in Article 74 paragraph (1) which only require PTs engaged in or related to natural resources to carry out CSR are inconsistent with the goals of the state as stipulated in the Preamble of the 1945 Constitution of the Republic of Indonesia, paragraph 3 regarding welfare. and prosperity, as well as being inconsistent with the 5th precept of Pancasila, therefore there must be an amendment to the article, making it obligatory for all or all PTs to carry out CSR. Then because the law exists for humans and not vice versa, the law must provide maximum benefits for humans, through its regulations using basic concepts of economics, to produce laws that are useful, efficient, valuable, and rational.